Can the Concentration of a Transcription Factor Affect Gene Expression? - Koşar, Zafer; Erbaş, Aykut (Frontiers in Soft Matter, 2022)
DNA is the ultimate molecule that encodes life through genes. Genes positioned along the meter-long DNA molecule have to be expressed at the right time and in the right amount via strict regulatory processes. Regulation of a gene starts with the binding of a DNA-binding protein known as a transcription factor (TF) to a target regulatory element along the double-stranded DNA molecule. Often, TFs attach to DNA in a sequence-specific manner and can target DNA motifs of various lengths, yet some TFs can also interact with DNA nonspecifically. The resulting DNA-TF complexes can control gene expression directly via controlling the recruitment of RNA polymerase on the target DNA sequence. Recent single-molecule experiments have added a new dimension to such control mode; the lifetime of a DNA-TF complex (i.e., the residence time of the protein on its DNA site) can function as a regulatory component. This breakthrough inevitably suggests that any physiochemical constituent that can alter the residence time of a DNA-binding protein can also be involved in gene regulation. In this perspective, we argue that a TF protein’s cellular concentration can contribute to the cell-scale transcription activity by modulating the DNA-residence time of the protein. Cells can achieve this either by enabling a concentration-dependent dissociation mechanism or by promoting the formation of multiprotein-DNA complexes. While our discussion here will consider examples from prokaryotic cells, we will also briefly argue that similar mechanisms could also be functional in eukaryotic cells.